From digital divide to digital capital: the role of education and digital skills in social media participation - Lybeck Robin; Koiranen Ilkka; Koivula Aki (Springer, 2025)
Social media platforms have become significant media for participating in society. This, and society's digitalization overall, has resulted in concerns regarding access and inclusion. By combining theories of social media participation and digital inequality, we explore issues regarding the prerequisites of participating through social media platforms, focusing especially on education. Through an analysis of data from a representative survey study in Finland (N = 3724), we illuminate the ambiguity of the perceived obstacles to both digital skills and political participation. We further build on the concept of digital capital to show the significant mediating effect of digital skills on education and participation. By utilizing the ISS (Internet Skills Scale), we break down digital skills into operational, information navigation, social, creative and mobile skills, and show how the operational skills have most significant mediator between education and political participation in social media. In studying digital inequality, we claim that the concept of digital capital is a valuable tool to illuminate the mechanisms for overcoming digital divides through the transaction of other forms of capital into digital capital, and digital capital to other forms of capital, in this case political capital.